Antimicrobial Efficacy of Propolis-Containing Varnish in Children: A Randomized and Double-Blind Clinical Trial. (26th April 2021) - Rodrigues Neto, Edilson Martins; Valadas, Lídia Audrey Rocha; Lobo, Patrícia Leal Dantas; Fonseca, Said Gonçalves da Cruz; Fechine, Francisco Vagnaldo; Lotif, Mara Assef Leitão; Bandeira, Mary Anne Medeiros; Mendonça, Julia Fontinele; de Mendonça, Karianne Marques; Fonteles, Marta Maria de França
Abstract : Dental caries is a sugar-dependent condition common in childhood, which causes microbiological imbalance in dental biofilm. The present study evaluated the antimicrobial efficacy of a 2.5% Brazilian Red Propolis (BRP) dental varnish to prevent caries in children. Seventy-five children with high caries risk, aged between 36 and 71 months and with no caries, were assigned to three groups to receive varnish treatment containing 2.5% BRP, 1% chlorhexidine, or 5% fluoride. The varnish was applied to the occlusal surfaces of the deciduous second molars on the first day of treatment (D1), after 90 days (D90), and 180 days of the start of treatment (D180). Saliva was collected to assess S. mutans before each varnish application and 180 days at the end of treatment (D360). Values were expressed in log10 (CFU/mL). Statistics were performed by applying repeated measures of variance analysis, Tukey's multiple comparisons test, and paired t -test. In the first dilution (1 : 10), there was microbial load reduction at the following periods: BRP in D0-D90 (p < 0.05 ) and D0-D180 (p < 0.01 ); fluoride in D0-D90 (p < 0.001 ); and chlorhexidine in D0-D180 (p < 0.05 ). In the second dilution (1 : 100), there was microbial load reduction in the groups at the following periods: BRP in D0-D90 (p < 0.05 ) and D0-D180 (p < 0.01 ); fluoride in D0-D180 (p < 0.05 ), and chlorhexidine in D0-180 (p < 0.01 ) and D0-360 (p < 0.05 ). The 2.5% BRP dental varnish was effective in decreasing S. mutans colonies in saliva when used within 90 days.